2021
DOI: 10.7150/thno.61690
|View full text |Cite
|
Sign up to set email alerts
|

A stem cell-derived ovarian regenerative patch restores ovarian function and rescues fertility in rats with primary ovarian insufficiency

Abstract: Rationale: Primary ovarian insufficiency (POI) normally occurs before age 40 and is associated with infertility. Hormone replacement therapy is often prescribed to treat vasomotor symptom, but it cannot restore ovarian function or fertility. Stem cell therapy has been studied for the treatment of POI. However, the application of live stem cells has suffered from drawbacks, such as low cell retention/engraftment rate, risks for tumorigenicity and immunogenicity, and lack of off-the-shelf feasibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The exploration of stem cell and stem cell-derived extracellular vesicle therapy in reproductive medicine has shown great promise and availability in preclinical and clinical trials to delay, prevent or even reverse ovarian aging (191,192). In preclinical trials, rhesus monkeys provide a suitable model for studying ovarian aging (193).…”
Section: Stem Cell Interventionsmentioning
confidence: 99%
“…The exploration of stem cell and stem cell-derived extracellular vesicle therapy in reproductive medicine has shown great promise and availability in preclinical and clinical trials to delay, prevent or even reverse ovarian aging (191,192). In preclinical trials, rhesus monkeys provide a suitable model for studying ovarian aging (193).…”
Section: Stem Cell Interventionsmentioning
confidence: 99%
“…122,123 Zhang et al encapsulated the secretome derived from MSCs in a decellularized surgical pelvic scaffold for fabrication of an ovarian patch to rescue primary ovarian insufficiency. 124 The ovarian patch could reduce local wound bleeding and tissue adhesion. Meanwhile, the released stem cell secretome protected ovarian function by inhibiting cell apoptosis and improving vascularization.…”
Section: Delivery Of Stem Cell Secretomementioning
confidence: 99%
“…Fibrin-based sealant patch had been reported to deliver exosomes for flexor digitorum profundus tendon healing, which could stably release extracellular vesicles for over 2 weeks . Liu et al loaded stem cell exosomes in a photo-cross-linked acellular scaffold, which retained exosomes within the defects for the long-term and effectively promoted cartilage regeneration. , Zhang et al encapsulated the secretome derived from MSCs in a decellularized surgical pelvic scaffold for fabrication of an ovarian patch to rescue primary ovarian insufficiency . The ovarian patch could reduce local wound bleeding and tissue adhesion.…”
Section: Delivery Of Stem Cell Secretomementioning
confidence: 99%
See 1 more Smart Citation
“…MSCs-derived ovarian regenerative patches (ORP) have been successfully applied to the repair of damaged ovarian. In a study by Zhang et al, [ 42 ] MSCs-derived ORP have great potential, they designed an ORP by embedding synthetic MSCs into a clinically approved surgical pelvic scaffold, and the result revealed that ORP can significantly ameliorate ovarian function by the stimulated proliferation of ovarian somatic and inhibited apoptosis under injury stress.…”
Section: The Applications Of Mscs In the Treatment Of Poimentioning
confidence: 99%